Agreement on the Retroactive Effect of Termination of the Contract in the Event of the Termination Condition; Its Rulings, Effects and Exceptions - mohsen esmaeili; Amirabbas Askari (پژوهشهای حقوقی)
The termination of the contract due to the termination clause has an effect on the future. The contract is valid until the condition of termination has not occurred. After the termination condition occurs, the contract will be terminated immediately and the effect of the termination will not be extended to the past. However, the parties to the contract may consider their interest in terminating the contract from the first day and agree that the contract will be terminated from the beginning if the condition of termination occurs. There is a difference in jurisprudence and law regarding the possibility of accepting such an agreement, and its rulings, effects and exceptions are not well defined. It is necessary to determine whether there is a possibility of agreement on the regressive effect of the termination of the contract due to the rescission condition or not, and then determine its rulings and effects. In this article, the analytical-descriptive method has been used from library sources, and while comparing the subject, the conclusion was reached that it is possible to generalize the effects of contract dissolution due to the termination condition compared to the past. The rulings, effects and exceptions of this matter have also been reviewed and explained.